Considering land use complexity and overlap is critical for sustainability planning - Pratzer, Marie (2025)
Land use is both a driver and a lever to address sustainability challenges like biodiversity loss, climatechange, and food security. Yet, it is often oversimplified in sustainability planning, ignoring the diversity ofactors or the multiple claims on land. We developed an approach to capture the complex and contested nature of land use by mapping it as social-ecological systems that can overlap in space. Demonstrating ourapproach for the Dry Chaco and Chiquitano forests in South America revealed three main insights. First,we mapped actors that are typically overlooked, such as forest-dwelling smallholders. Second, substantialland use overlap, particularly between smallholders and agribusinesses, signals land competition that risksmarginalizing smallholders. Third, our maps showed conservation areas overlapping with other land systems, highlighting opportunities for co-benefits but also competition. Overall, our transferable approach captures land use complexity and visualizes often overlooked actors, thereby potentially contributing to morejust and effective sustainability planning.